PENGARUH PARTISIPASI ANGGARAN DAN AKUNTANSI PERTANGGUNGJAWABAN TERHADAP KINERJA MANAJERIAL - Lukito, Mega Satrio; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of budget participation and responsibility accounting to the managerial performance on the Dinas PU Pengairan Provinsi Jawa Timur. The quantitative method is used as the research method. The population is the employees who have authorities in preparing the budget on Dinas PU Pengairan Provinsi Jawa Timur and 36 people have been selected as samples. The sample collection technique has been done by using purposive sampling. The analysis technique has been done by using multiple linear regressions. The result of the test shows that budget participation variable has positive and significant influence to the managerial performance. The responsibility accounting has positive and significant influence to the managerial performance. This condition is shown by the significance level of each variable is under Î± = 5%. When budget participation which has been done by the employees is getting high it will increase the managerial performance and the responsibility accounting has been implemented is getting better, it will improve the managerial performance.Keywords: Budget Participation, Responsibility Accounting, Managerial Performance.